2022
DOI: 10.1111/tops.12629
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Complexity Perspective on Segmentation as a Cognitive Subcomputation

Abstract: Computational feasibility is a widespread concern that guides the framing and modeling of natural and artificial intelligence. The specification of cognitive system capacities is often shaped by unexamined intuitive assumptions about the search space and complexity of a subcomputation. However, a mistaken intuition might make such initial conceptualizations misleading for what empirical questions appear relevant later on. We undertake here computational‐level modeling and complexity analyses of segmentation — … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…In this chapter, we have attempted to clarify the computational challenges posed by online speech inference, to propose how listeners solve these challenges, and to integrate these possible solutions in a mechanistic model of word segmentation, Vowel-onset Paced Syllable Inference. In the context of online speech processing, we have suggested that strict temporal constraints advantage computational efficiency, above and beyond tractability or computability [49]. Like others before us [47,48,52,70,73,84], we have highlighted the cost of search operations [172], the size of the search space, and the speed-accuracy tradeoff.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…In this chapter, we have attempted to clarify the computational challenges posed by online speech inference, to propose how listeners solve these challenges, and to integrate these possible solutions in a mechanistic model of word segmentation, Vowel-onset Paced Syllable Inference. In the context of online speech processing, we have suggested that strict temporal constraints advantage computational efficiency, above and beyond tractability or computability [49]. Like others before us [47,48,52,70,73,84], we have highlighted the cost of search operations [172], the size of the search space, and the speed-accuracy tradeoff.…”
Section: Discussionmentioning
confidence: 53%
“…A particular challenge posed by word segmentation, and one absent from many theoretical accounts [33,48,49], is the necessity for online inference: linguistic signals arrive sequentially, vanishing after momentary articulation; listeners must make sense of the current input before it is overwritten by the next [50][51][52]. Results have suggested a central role for the syllabic timescale in both the pacing of speech and its intelligibility [1-6, 12, 15, 16, 53-56], with experiments on so-called repackaged speech suggesting an upper limit on the speech "information rate" of ∼9 syllables per second [15,57].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Computational modelling of capacities can help us to make our assumptions precise and explicit, and to draw out their consequences, without the need to simulate the postulated computations (though simulations have their uses; more on that next). For instance, with formal computationallevel models and mathematical proof techniques at hand, one can critically assess claims of explanatory adequacy Egan, 2017;van Rooij & Baggio, 2021), claims of intractability (Adolfi, Wareham, & van Rooij, 2023), claims of tractability van Rooij, Evans, Muller, Gedge, & Wareham, 2008), claims of competing theories , claims of evolvability (Rich, Blokpoel, de Haan, & van Rooij, 2020;Woensdregt et al, 2021), and claims of approximability (Kwisthout & Van Rooij, 2013;Kwisthout, Wareham, & Van Rooij, 2011). 16 We acknowledge that computational modelling can also contribute to productive theory development without committing to computationalism (Guest & Martin, 2021;Morgan & Morrison, 1999).…”
Section: Theory Without Makeingmentioning
confidence: 99%
“…This is no magic bullet, however; underdetermination of theory by data cannot be eliminated, and any ways of dealing with it will remain necessarily incomplete (cf. Adolfi, Wareham, & van Rooij, 2023;Devezer, 2023;Rich et al, 2021).…”
Section: Underdeterminationmentioning
confidence: 99%